Umbilical vein remodeling is associated with pregestational maternal overweight - Souza, Kamilla Batista da Silva; Hochberger, Luana Caroline; Castrignano Camargo, Felippe Egon; Silva, Gabriely Santos; Camargo, Giovanna Castrignano; Mello, João Pedro Lourenço; Alcantara Dos Santos, Fernanda Cristina; Giachini, Fernanda Regina; Lobato, Núbia de Souza; Souto, Paula Cristina de Souza (Frontiers in Endocrinology, 2024)
Introduction Excess weight during pregnancy is a condition that can affect both mother and fetus, through the maternal-fetal interface, which is constituted by the placenta and umbilical cord. The umbilical vein is responsible for transporting oxygen and nutrients to the fetus, and its proper functioning depends on the integrity of its structure. The remodeling of the umbilical vein represents one of the causes of inadequate transport of nutrients to the fetus, being potentially harmful. This study aims to evaluate whether maternal overweight alters the structural characteristics of the umbilical vein. Methods Umbilical cords were collected from eutrophic and overweight pregnant women and were processed according to histological routine. We analyzed morphometry parameters, collagen and elastin fibers deposition, glycosaminoglycan level, and cell proliferation. Results Veins from overweight pregnant women were found to have greater total area, wall area, wall thickness, and diameter. There was higher collagen labeling in the perivascular region of the overweight group and a higher amount of type III collagen in the vascular smooth muscle. The proliferation of muscle and perivascular cells was higher in overweight pregnant women. A positive, although weak, correlation was observed between BMI and vessel thickness and with type III collagen deposition in vascular smooth muscle. Discussion With this study, we show that being overweight can structurally alter the umbilical vein, causing vascular remodeling of the vessel, through hypertrophy and hyperplasia.